Upaya Penegakan Hukum terhadap Tindak Pidana Pencurian dengan Pemberatan - Fajar Ammar Ikhsanuddin Al Aslami (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Aggravated theft is a criminal act of theft that involves certain elements which make it a more serious crime and subject to heavier penalties than ordinary theft. Usually this theft is carried out by two or more people. The crime of theft is aggravated as a crime against property, where qualifying theft is carried out in certain ways and under certain circumstances so that it is threatened with a heavier crime compared to ordinary theft. Second, the application of sanctions for criminal acts of theft with weighting begins with proving theft in its basic form which has fulfilled the elements, as stated in the court decision in the theft case as from the results of research, by imposing a crime as stated in the regulations in the criminal law (KUHP), and fulfill the elements in the article for the crime of aggravated theft based on the evidence at trial and based on the judge's belief.